2020
DOI: 10.1038/s41586-020-2927-z
|View full text |Cite
|
Sign up to set email alerts
|

Host ANP32A mediates the assembly of the influenza virus replicase

Abstract: Aquatic birds represent a vast reservoir from which novel pandemic influenza A viruses can emerge 1 . Influenza viruses contain a negative-sense segmented RNA genome which is transcribed and replicated by the viral heterotrimeric RNA polymerase (FluPol) in the context of viral ribonucleoprotein (vRNP) complexes 2 , 3 . RNA polymerases of avian influenza A viruses (FluPol A ) replicate viral RNA poorly in hum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
188
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(232 citation statements)
references
References 62 publications
8
188
0
Order By: Relevance
“…The RdRp domain uses the priming loop to stabilize the pppApG initiation product [ 30 ]. Recent structural evidence has also revealed that host protein ANP32A must bind to the RNA polymerase residing in the vRNP in order to recruit a newly synthesized RNA polymerase [ 56 ]. This process leads to the formation of a viral RNA polymerase dimer that likely facilitates the transfer of the emerging 5′ terminus of the nascent strand to the new RNA polymerase and the formation of a cRNP [ 11 , 56 , 57 ].…”
Section: The Viral Rna Polymerase and Mechanisms Of Rna Synthesismentioning
confidence: 99%
See 2 more Smart Citations
“…The RdRp domain uses the priming loop to stabilize the pppApG initiation product [ 30 ]. Recent structural evidence has also revealed that host protein ANP32A must bind to the RNA polymerase residing in the vRNP in order to recruit a newly synthesized RNA polymerase [ 56 ]. This process leads to the formation of a viral RNA polymerase dimer that likely facilitates the transfer of the emerging 5′ terminus of the nascent strand to the new RNA polymerase and the formation of a cRNP [ 11 , 56 , 57 ].…”
Section: The Viral Rna Polymerase and Mechanisms Of Rna Synthesismentioning
confidence: 99%
“…Recent structural evidence has also revealed that host protein ANP32A must bind to the RNA polymerase residing in the vRNP in order to recruit a newly synthesized RNA polymerase [ 56 ]. This process leads to the formation of a viral RNA polymerase dimer that likely facilitates the transfer of the emerging 5′ terminus of the nascent strand to the new RNA polymerase and the formation of a cRNP [ 11 , 56 , 57 ]. No polyadenylation takes place during cRNA synthesis and elongation continues until the vRNA template has been fully copied, which implies that the 5′ end of the vRNA needs to be released from its binding pocket during cRNA sythesis.…”
Section: The Viral Rna Polymerase and Mechanisms Of Rna Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…ANP32 proteins are known to carry out various roles such as chromatin regulation, phosphatase regulation, involvement in apoptosis and intracellular transport [ 318 ]. ANP32A was initially discovered to be a major co-factor of IAV determining species specificity [ 319 ], mediating the assembly of the IAV replicase [ 320 ].…”
Section: Iav Restriction Factorsmentioning
confidence: 99%
“…Interestingly, the interaction between ANP32A and the viral RNA polymerase is significantly strengthened in the presence of viral RNA (26,33), suggesting that ANP32A binds the RNA polymerase in the context of an RNP. Recent cryo-electron microcopy structures of an influenza C virus RNA polymerase dimer revealed that ANP32A formed a bridge between an RNA polymerase bound to RNA and an apo form of the RNA polymerase (7), suggesting that ANP32A mediates the assembly of the viral replicase complex.…”
Section: Introductionmentioning
confidence: 99%